MYCOSIS FUNGOIDES PROGRESSING TO PERIPHERAL T-CELL LYMPHOMA AND THE POTENTIAL ROLE OF ROMIDEPSIN THERAPY - Bengisu Ece Duman; Ceren Deveci; Birol Güvenç (Hematology, Transfusion and Cell Therapy)
Introduction: PTCL-NOS is an uncommon and highly aggressive kind of non-Hodgkin lymphoma. Transformation of MF, a cutaneous T-cell lymphoma, into systemic PTCL is infrequent and poses serious challenges both diagnostically and therapeutically. This report describes the challenges in diagnosis and therapy of a transformation case from MF to PTCL which responded to romidepsin. Case Report: A 58-year-old male presented to the OPD in the year 2022 with complaints of chronic itching. Skin biopsy diagnosis was lichen planus. Further skin biopsies done in the year 2023 established mycosis fungoides with patch-stage disease. Thereafter, the disease evolved to involve lymph nodes within a year. Excisional biopsies of these lymph nodes showed dermatopathic lymphadenopathy, which later was transformed into T-cell lymphoid neoplasia indicating transformation into PTCL-NOS. Immunohistochemical analysis showed positivity for CD3+, CD4+, CD7+, GATA3+, and Ki-67 expression. CD30 was negative.In spite of first-line therapies administered, such as photopheresis, methotrexate, and PUVA, the disease further progressed, as indicated in the PET-CT scan with increased metabolic activity in multiple lymph nodes and cutaneous thickening. The patient was initiated with romidepsin—a histone deacetylase inhibitor—on salvage therapy for PTCL. The current follow-up represents clinical stability, with no development of new lesions or disease progression. Discussion: The case serves to underline the complex evolution as seen from mycosis fungoides to systemic PTCL and challenges in the management of refractory disease. Use of romidepsin underlines the potential of epigenetic therapies in the treatment of advanced T-cell lymphomas, especially in relapsed or refractory states. The patient's journey underlines the importance of early diagnosis, a multidisciplinary approach, and adaptive treatment strategy in the management of these aggressive lymphomas.